Approximated Backscattered Wave Models of a Lossy Concentric Dielectric Sphere for Fruit Characterization - Hoang Nam Dao; Chuwong Phongcharoenpanich; Monai Krairiksh (My University, 2022)
Approximated models of electromagnetic waves scattered from a sphere with two different dielectric layers were developed and reported in this paper. We proposed that the dielectric properties of a concentric dielectric sphere object, for example, some types of fruit, could be estimated by this model, from some wave components of the backscattered wave. The models were suitable for lossy objects because only a single bounce of the wave was assumed. In terms of first bounce as well as total backscattered wave results, the reported values agreed well with the values calculated by a commercial software. The measurement results verified the calculated wave components. The dielectric properties determination of real fruits was performed and exhibited the potential in fruit characterization. The main advantage of these models is that they can provide the magnitude and phase information of each backscattered wave component, which makes quality monitoring of fruits to be possible.
Keywords: Lossy compression; Characterization; Soil Moisture and Remote Sensing